Evaluation of Pharyngeal Airway Volume Three-Dimensionally in Various Sagittal Skeletal Patterns - Systematic Review - Balaji Rajkumar; Ratna Parameswaran; Mary Sanjana; Srinivasan Boovaraghavan; Devaki Vijayalakshmi (Indian Journal of Dental Research)
To investigate the pharyngeal airway volume in different anteroposterior skeletal malocclusions. This study was prepared according to the Cochrane criteria for creating a systematic review and meta-analysis and confirms the preferred reporting items for systematic reviews and meta-analyses (PRISMA) statement. This search was conducted to answer the patient/population, intervention, comparison and outcomes (PICO) question: To evaluate (outcome) and compare (comparison) whether there is a difference in airway volume in patients (participants) with different skeletal malocclusions diagnosed using 3D data (intervention). The first two authors extracted the data from the included studies and assessed the risk of bias in the individual studies using the Newcastle-Ottawa scale. Meta-analysis was done using STATA version 16, which compared various three-dimensional pharyngeal airway parameters in skeletal Class II and skeletal Class III malocclusions with that of skeletal class I malocclusion. Out of 370 articles from the initial search, 17 articles were included in the systematic review. Out of 17 studies, 12 eligible studies were included in the quantitative synthesis. The nasopharynx, oropharynx, hypopharynx, and total airway volume were increased in skeletal Class I malocclusion compared to that of skeletal Class II malocclusion and decreased in comparison to skeletal Class III malocclusion. The moderate quality of evidence indicates the total airway volume, oropharynx, and hypopharynx are largest in skeletal Class III compared to Class I and Class II skeletal malocclusion.